Fenomena dan Pandangan Pria dalam Menonton Drama Korea - Qorib, Fathul; Olievia, Fitri (Yayasan Lentera Avanya Nagari, 2023)
Women often consider Korean drama films more preferred because the stories focus on romance, emotions, and interpersonal relationships. Male fans of Korean drama films are considered new and unique, but a negative stigma is often attached to them in Indonesia. Labels such as